An oxidation protective coating prepared by SiC densifying HfB2-SiC skeleton for SiC-coated C/C composites at 1473, 1773, and 1973 K. (October 2022) - Zhu, Xiaofei; Zhang, Yulei; Qiang, Xinfa; Zhang, Jian; Su, Yangyang; Li, Tao
Abstract: A HfB2 -SiC skeleton was designed on SiC-coated C/C composites using hollow SiO2 microspheres as sacrificial templates, which was densified by SiC via chemical vapor infiltration to fabricate a dense SiC-HfB2 oxidation protective coating. In this way, the uniform distribution of HfB2 in the coating was realized. Cracks in the SiC inner coating were covered by the SiC-HfB2 coating; Hf-oxides improved the stability and inhibited the volatilization of SiO2 in the compound glass layer. Therefore, the coating can protect C/C composites against oxidation for 59 h at 1473 K, 503 h at 1773 K, and 166 h at 1973 K. Highlights: A HfB2 -SiC skeleton is prepared on SiC-coated C/C composites using hollow SiO2 microspheres as sacrificial templates. A dense SiC-HfB2 coating with uniform distribution of HfB2 is fabricated by SiC densifying HfB2 -SiC skeleton at low temperature. Hf-oxides improve the high-temperature stability of SiO2 glass for reducing its volatilization. The SiC-HfB2 coating can protect C/C composites against oxidation at 1473, 1773, and 1973 K.